Plant and Soil Science Research Results 1978-79, Southeastern Kansas Branch - K. W. Kelley; R. J. Johnson (Kansas Agricultural Experiment Station Research Reports, 1979)
Crop research in Southeast Kansas, Mound Valley.
Keywords: corn; grain sorghum; soybeans; wheat